HUBUNGAN NILAI CE DENGAN LAPISAN KULIT THIN WALL DUCTILE IRON - Fadhlan, Muhammad; Sulamet-Ariobimo, Rianti Dewi; Oktaviano, Yoska (POROS, 2023)
The formation of skin effects in nodular cast iron produced using sand molds is a general problem. Since it can be cleaned during the machining process along with gating system removal. Skin effects become a problem when they form in nodular cast iron thin wall castings. In thin-wall castings, the skin effect becomes a problem because the cleaning process is difficult to perform. Therefore, a mechanism is needed to avoid the formation of skin effects in nodular cast iron thin wall castings. This work is carried out to see the effects of carbon equivalent (CE) as one of the important parameters during the casting process to the formation of skin effects, especially when the cast object produced is a component. Molten metals with different CE values are used to make thin wall ductile iron connecting rod components. Microstructure observations were carried out both in the I-beam and end-rod areas. Then the results obtained are compared with the previous research regarding the skin effects formed in thin-wall ductile iron plates. The result obtained is that the skin effects detected in thin-wall ductile iron connecting rods with different types of patterns and thicknesses from that formed on the plate.